The Repetition of the Dialogue ‘Hi, I’m Sore’ as a Dramaturgical Technique in Character Development in the Movie Sore: Wife from the Future: Repetisi Dialog “Hai, Aku Sore” Sebagai Teknik Dramaturgi dalam Pengembangan Karakter Film Sore: Istri Dari Masa Depan - Chelsea Nakita; Arsenia Yulia Pramesti; Erlina Santi Rahmadani; Fadila Nuriska; Nur Arif Anandhita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the function of the repeated dialogue “Hi, I’m Sore…” as a dramaturgical technique in character development in the film Sore: Wife from the Future and to examine its implications for performing arts education. The film Sore depicts a woman (the Wife) trapped in a romantic time travel scenario in an effort to save Jo (the Husband). Repetition in a performance piece is not merely textual repetition but a dramatic device capable of building emotional intensity, intensifying conflict, and marking the transformative development of a character. This study employs a qualitative method with a dramaturgical analysis approach, focusing on the development of conflict and shifts in the meaning of dialogue with each recurrence. Data collection techniques involved textual and visual observation of scenes containing the dialogue in question. The results indicate that the same dialogue undergoes a shift in meaning as the relationships between characters and the dynamics of conflict evolve, thereby functioning as a dramatic strategy to underscore the characters’ psychological growth. Furthermore, these findings hold pedagogical relevance for performing arts education, particularly as a model for exercises in emotional exploration and textual interpretation for performing arts students. Dialogue repetition can be utilized as a training method to understand character transformation through variations in intensity, gestures, and different dramatic contexts. Thus, this study affirms that the technique of repetition in film can serve as a conceptual and practical reference in the development of performing arts teaching strategies. The analysis shows that repetition appears in the form of the repetition of daily habits in dialogue, situations, and interactions between characters. This repetition is not static but rather a shift in meaning that reflects the psychological development of the character’s role. Jonathan’s character transformation is evident in stages, evolving from an indifferent attitude to one that is more self-aware, reflective, and responsible for his life.